Effect of a Ventilatory Assist Device in Addition to Supplemental Oxygen on Exercise Endurance in Subjects With COPD - Hilling, Lana; Cayou, Cindy; Kops, Richard S; Ameo, Robert A; Morishige, Richard J; Glezer, Stanislav; Hill, Nicholas S (Respiratory care, 2024)
This study assessed the clinical effects of a ventilatory assist (VA) device in addition to supplemental O (VA+O ) on exercise endurance in subjects with severe to very severe COPD managed with long-term oxygen therapy (LTOT). This was a crossover clinical feasibility study of the effects of VA+O in subjects with severe to very severe COPD managed with LTOT ( 15). At visit 1, physiologic measures were obtained, and subjects were tested on the cycle ergometer with VA. Peak work rate and flow for continuous supplemental O /VA+O were established. At visit 2, subjects exercised at a constant work rate of 80% peak work rate to maximum endurance after allocation to VA+O or O . Cardiorespiratory variables, work rate, and dyspnea were included to define potential clinical benefits of VA+O . Data were analyzed using a linear mixed model. Fifteen subjects with COPD (mean ± SD, age 67.9 ± 9.0 y, FEV 0.89 ± 0.35 observed) completed the study. Exercise duration in minutes was significantly longer with VA+O versus O (least squares mean [standard error], 12.0 [2.0] vs 6.2 [2.0], = .01). VA+O versus O was also associated with significantly greater isotime improvements in Borg dyspnea scores (3.6 [0.5] vs 5.7 [0.5] < .001), S (96.9 [0.9] vs 91.4 [0.9] < .001), leg fatigue scores (3.8 [0.6] vs 5.2 [0.6] = .008), and breathing frequency (22.8 [0.9] vs 25.8 [0.9] breaths/min = .01). There were no differences in heart rate. In symptomatic subjects with severe to very severe COPD, VA+O significantly increased exercise time and improved dyspnea, S , breathing frequency, and leg fatigue versus O alone.